Narration in the novel ”Soad and the military” by Najm Wali : Critical study (Raparin Journal of Humanities (RJH), 2024)
This research deals with addressing the character in the novel (Suad and the Military) by the expatriate Iraqi novelist (Najm Wali)، who is considered one of the well-known novelists in the Arab world in general and in Iraq in particular، especially outside the Arab world.The research plan is based on three types of characters: (the main character)، (the secondary character)، and (the developing character)، and is preceded by an introduction to the novelist character، as it is one of the most important and important narrative components in the novel، as it specializes in the study of characters from The external and internal aspect and the effective role that it possesses to reach the detection of various aspects، such as the psychological aspect and to clarify the various individual differences، by distinguishing between the external physical image، and the internal psychological image، and through the novelist's description of it. And its role in taking positions in order to reach a complete picture of it and its definition in the linguistic perspective، and then the terminology، followed by the most important results reached by the research، and the references used in it.* Najim Wali، born in 1956، was born in the city of Al-Amara، left Iraq in 1980 and now resides in Germany. He holds a BA in German literature from the German (Hamburg University) and Spanish literature at (Completense University) in Madrid. Concordia) in (2018)، and his novels: (The War in the Tarab neighborhood) in (1989)، (A place called Kumait) in (1997)، (Tal Lahem) in (2001)، and (The Picture of Youssef) in (2005). )، (Angels of the South) (2009)، (Baghdad Malboro) (2012)، (Sarah’s Sin) (2018)، and two short story collections: (Mary’s Last Night) (1994)، and (Waltz with Matilda) (1999)، (The Book of Baghdad، a Civilian Biography) in (2015)، and finally his novel (Suad and the Military)، which is his last work، as it was published last year.